Synthesis and Properties of New Multifunctional Hexaferrite Powders. (2015) - Li, J.; Zhang, H.-F.; Shao, G.-Q.; Chen, D.; Zhao, G.-G.; Gao, Z.-S.; Liu, J.-H.; Lu, J.-S.; Li, X.-B.
Abstract: Sr3 Co2 Fe24 O41 (Sr3 Co2 Z) hexaferrite has potential applications in spintronics and multiferroics. To synthesize a single-phase Sr3 Co2 Z is very difficult now while the corresponding reaction process lacks investigating. In this work, the reaction mechanism to synthesize Z/W/M-type strontium hexaferrite powders was studied. Results show that the SrFe12 O19 (SrM) could react with CoFe2 O4 to form SrCo2 Fe16 O27 (SrCo2 W) in the range 750 o C < T < 1150 o C. The SrCo2 Fe16 O27 (SrCo2 W) transforms into Sr3 Co2 Z in the range 1150 o C < T < 1250 o C.